Recognising older people's individual resources and home-care-specific tasks in home care in Finland: A document analysis of care and service plans - Puustinen Jonna; Kangasniemi Mari; Pasanen Miko; Turjamaa Riitta (Wiley, 2025)
Background and Rationale: Comprehensive care and service planning in home care is tailored to older people's individual needs and resources in order to support them living at home. However, little is known about how these individual resources and home-care-specific tasks are recognised in older people's care and service plans.
Aims: To describe the content of care and service plans in older people's home care with special attention to their individual resources and home-care-specific tasks.
Design: This was a document-based cross-sectional study with mixed-methods analysis, carried out in Eastern Finland during Spring 2018.
Methods: A document analysis using the deductive Finnish Care Classification (FinCC), and an inductively developed framework of older people's care and service plans (n = 71). The data were analysed with descriptive statistical methods.
Results: Altogether, 1718 notes were relevant to the FinCC main categories: 707 (41%) focused on older people's needs and 1011 (59%) on nursing interventions. We identified 1104 notes based on the 26 inductively developed main categories: the majority (n = 628, 57%) focused on individual resources and the remainder (n = 476, 43%) on home-care-specific tasks. Increasing age resulted in fewer notes on safety and sensory functions. There were fewer notes on resources related to sleeping and wakefulness after longer care and service periods. An increased number of home visits resulted in more documentation on tasks related to pharmaceutical issues, including repeat prescriptions.
Discussion: Individual resources for older people were documented, to some extent, in their care and service plans. It is necessary to review these alongside home-care-specific tasks that support older people's independence and safety at home.
Conclusion: Individual resources need to be recognised in order to enable home-care professionals to provide tailored, high-quality home care services. Home-care-specific tasks should be supported by documentation with updated, sensitive home care classifications.